Estudo da percepção dos médicos com necessidades educacionais especiais sobre a sua formação e atuação médica - Mariano, Nayara Neves (2020)
Currently, due to changes in Brazilian educational legislation, the increase in number of students with disabilities in University Education is increasingly evident. However, the full access and permanence of people with disabilities in University Education is not yet a reality. In Medicine, there are few studies related to inclusion strategies of students with disabilities. This work aimed to analyse the perception of physicians with physical disabilities (motor, visual or hearing) in Higher Education, identifying obstacles and strategies for personal coping during the professional training process and after entering the job market. The study is of a qualitative and phenomenological kind and 8 physicians with congenital or acquired physical disabilities, during or prior to the medical course, were selected to be interviewed. Data collection took place over 4 months along 2019 and were analysed using the content analysis technique. 8 interviews were carried out with doctors of different specialties, 4 men and 4 women, aged between 31 and 55 years. Most of the doctors interviewed did not receive support from a specific program during graduation years and faced prejudice in classroom as well as in the job market. However, it was evident that support network built by family members, colleagues and teachers were of great importance in addressing the existing architectural and pedagogical barriers. We could infer that the best course of action is to discuss with the physical disabled student what is his o her real needs to organize an individualized course of action. It is believed that having more people with disabilities in higher education plays an essential role in the inclusion process and that understanding their point of view in academic and professional path can be a promising resource in overcoming the still existing inequalities